Analysis of Beef Cattle Fattening Business - Pateda, Sri Yenny; Ilham, Fahrul; Zakaria, Fauzan; Singgili, Haris (Jambura Journal of Animal Science, 2025)
The cattle fattening business in Limboto District is predominantly managed by farmers through farmer groups. These fattening groups are spread across several villages, including Hutabohu Village, where the Ilohelumo group operates. Beef cattle fattening is a viable strategy to enhance community income, as it involves specific inputs and produces outputs in the form of revenue and business profits (Abidin, 2012). This study employed a case study method, with the research location selected through purposive sampling based on the presence of a successful cattle fattening group. The selected location was Hutabohu Village in Limboto District, Gorontalo Regency. The respondents were selected using total sampling from the Ilohelumo group, consisting of 20 members. The analytical methods used included descriptive analysis, income analysis, Return on Revenue (ROR), Break Even Point (BEP), Return Cost Ratio (R/C), and Benefit Cost Ratio (B/C). The Ilohelumo cattle fattening group managed 20 heads of cattle with a total production cost of IDR 215,300,000, comprising both fixed and variable costs. The group generated a profit of IDR 118,223,112 per fattening period, or approximately IDR 5,911,155 per head per month. The business achieved an R/C ratio of 2.864 and a B/C ratio of 1.482, indicating that the beef cattle fattening enterprise is profitable and financially feasible.